2015
DOI: 10.1021/acs.jpcc.5b05823
|View full text |Cite
|
Sign up to set email alerts
|

Collective Behavior of Molecular Dipoles in CH3NH3PbI3

Abstract: Using ab-initio molecular dynamics, we report a detailed exploration of the thermal motion occurring in perovskite crystals of formula CH 3 NH 3 PbI 3 . We exploit the data generated to obtain estimates of the rotational relaxation time of the cation CH 3 NH + 3 . We examine the tetragonal and cubic phase, as both may be present under operational conditions. Influenced by each other, and by the tilting of PbI 6 octahedra, cations undergo collective motion as their contribution to polarization does not vanish. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 34 publications
5
52
0
Order By: Relevance
“…Recent reports show that even without defects, hybrid perovskite crystals display significant structural fluctuations [3][4][5][6][7][8][9][10][11][12][13][14]. The organic molecular cation plays an important role in the structural fluctuations of the hybrid perovskites, as supported by dielectric measurements, neutron scattering, and molecular dynamics [15][16][17][18].…”
mentioning
confidence: 89%
“…Recent reports show that even without defects, hybrid perovskite crystals display significant structural fluctuations [3][4][5][6][7][8][9][10][11][12][13][14]. The organic molecular cation plays an important role in the structural fluctuations of the hybrid perovskites, as supported by dielectric measurements, neutron scattering, and molecular dynamics [15][16][17][18].…”
mentioning
confidence: 89%
“…Some theoretical works investigated the distribution and rotation of organic cations, [208][209][210][211][212][213][214] and found that rotational relaxation time in the tetragonal and cubic phases are 32.7 and 15.2 ps, respectively. [208] The rotational motions of MA cations suppressed the thermal conductivity. [213] The energy landscape and the band structure are relatively insensitive to the A-cation orientation.…”
Section: Distribution and Rotation Of Organic Cationsmentioning
confidence: 99%
“…Ferroelectricity is another potential cause considered for the observed hysteresis. Yet it is a controversial hypothesis, as the time-scales involved are typically below ms [26], which lends the idea of microscopic ferroelectricity [27]. It is important to note, however, that capacitive effects alone cannot reproduce different pre-conditioning effects induced by initial light soaking and pre-poling by different biases [19].…”
Section: Introductionmentioning
confidence: 99%